2015
DOI: 10.1364/ome.5.000996
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hierarchical photonic nanostructures inspired by Morpho butterflies utilizing laser interference lithography

Abstract: Abstract:We introduce laser interference lithography (LIL) as a tool to fabricate hierarchical photonic nanostructures inspired by blue Morpho butterflies. For that, we utilize the interference pattern in vertical direction in addition to the conventional horizontal one. The vertical interference creates the lamellae by exploiting the back reflection from the substrate. The horizontal interference patterns the ridges of the hierarchical Christmas tree like structure. The artificial Morpho replica produced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
(64 reference statements)
0
41
0
Order By: Relevance
“…However, to create blue reflection from a similar structure, longitudinal and transverse dimensions of the microribs need to be sufficiently large. This statement is supported by the Morpho butterfly structural pattern as a very good natural example of such architecture, as well as by several experimental biomimetic structures123132. It was also reported that the origin of the intense and directional blue reflection of Hypolimnas bolina is similar kind of complex structures22.…”
Section: Discussionmentioning
confidence: 66%
“…However, to create blue reflection from a similar structure, longitudinal and transverse dimensions of the microribs need to be sufficiently large. This statement is supported by the Morpho butterfly structural pattern as a very good natural example of such architecture, as well as by several experimental biomimetic structures123132. It was also reported that the origin of the intense and directional blue reflection of Hypolimnas bolina is similar kind of complex structures22.…”
Section: Discussionmentioning
confidence: 66%
“…31 Single beam, or multibeam laser light has been utilized to produce interference patterns to ablate 2D/3D nanopatterns. 30,32,[39][40][41][42] Laser ablation can be utilized to form nanophotonic devices in ink, gold, polymers, or functionalized substrates. 35,[42][43][44][45] The patterned geometries depend on the laser properties (ablation energy, laser wavelength, spot size), and structural parameters (distance, height, and recording angle).…”
mentioning
confidence: 99%
“…31,35 However, multibeam interference require precise exposure angles to create complex nanostructures. 39 Here, 3D stacked rings in a hexagonal arrangement were produced through multibeam interference based holography and copies were imprinted through roll-to-roll processing over 4 large areas of a flexible polymeric film. The patterned photonic nanostructures focused light and acted as SMLA.…”
mentioning
confidence: 99%
“…The undercut helps to prevent adhesion of the metal pattern to the lithographic mask, while the etching mask can be patterned by various methods such as nanoimprint, UV, and E‐beam lithography . In the case of periodic (repetitive) patterns, laser interference lithography can also be utilized to effectively treat large surfaces without the use of cost‐intensive masks . As an alternative, lift‐off processes can be used for undercut formation without silicon etching.…”
Section: Introductionmentioning
confidence: 99%